2018
DOI: 10.3390/toxins10020065
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Current Methods for Analysis of Mycotoxins in Herbal Medicines

Abstract: The presence of mycotoxins in herbal medicines is an established problem throughout the entire world. The sensitive and accurate analysis of mycotoxin in complicated matrices (e.g., herbs) typically involves challenging sample pretreatment procedures and an efficient detection instrument. However, although numerous reviews have been published regarding the occurrence of mycotoxins in herbal medicines, few of them provided a detailed summary of related analytical methods for mycotoxin determination. This review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
173
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(177 citation statements)
references
References 176 publications
(231 reference statements)
1
173
0
3
Order By: Relevance
“…In 1993, the International Agency for Research on Cancer reported AFB 1 as a Class 1 carcinogen [13], since it is 68-fold more toxic than arsenic, second only to botulinum, and is currently the most toxic mycotoxin. The 2015 edition of the Chinese Pharmacopoeia has specified 14 types of medicinal materials including Nelumbinis semen, Myristicae semen, and Jujubae fructus, and five types of animal medicinal materials such as Hirudo to detect AFs, and established a permissible limit of 10 µg kg −1 in these medicinal material [10]. Approximate 70.8% (34/48) of medicinal herbs in this study were slightly contaminated with aflatoxins (<5 µg/kg).…”
Section: Mycotoxigenic Potentials Of the Fungal Isolatesmentioning
confidence: 81%
See 1 more Smart Citation
“…In 1993, the International Agency for Research on Cancer reported AFB 1 as a Class 1 carcinogen [13], since it is 68-fold more toxic than arsenic, second only to botulinum, and is currently the most toxic mycotoxin. The 2015 edition of the Chinese Pharmacopoeia has specified 14 types of medicinal materials including Nelumbinis semen, Myristicae semen, and Jujubae fructus, and five types of animal medicinal materials such as Hirudo to detect AFs, and established a permissible limit of 10 µg kg −1 in these medicinal material [10]. Approximate 70.8% (34/48) of medicinal herbs in this study were slightly contaminated with aflatoxins (<5 µg/kg).…”
Section: Mycotoxigenic Potentials Of the Fungal Isolatesmentioning
confidence: 81%
“…In the case of medicinal plants, official regulations regarding the presence of only aflatoxins and OTA in medicinal herbs are shared globally among pharmacopoeias and national and organizational regulations. In general, the current legal limit for AFB 1 in medicinal herbs ranges between 2 µg kg −1 and 10 µg kg −1 , while the limit for total aflatoxins (combined AFB 1 , AFB 2 , AFG 1 , and AFG 2 ) ranges from 4 µg kg −1 to 20 µg kg −1 , and the limit for OTA rangs from 15 µg kg −1 to 80 µg kg −1 [10]. Herein, 70.8% (34/48) of medicinal herbs were contaminated with AFB 1 ; however their levels were within the permissible limits (5 µg kg −1 ).…”
Section: Introductionmentioning
confidence: 99%
“…The QuEChERS method includes two steps-a simultaneous extraction and partitioning step using acetonitrile and salts, followed by a clean-up step based on a dispersive solid-phase extraction (dSPE) [30,32]. Following the acetonitrile extraction step, different sorbents, such as octadecyl silica (C18), primary secondary amine (PSA), and graphitized carbon black (GCB), can be used for additional purification, which can result in satisfactory recoveries due to the reduced matrix effect [31].…”
Section: Extractionmentioning
confidence: 99%
“…The most significant fungi here belong to the following stems: Aspergillus, Penicillium, Fusarium, Alternaria and Claviceps [1]. A MT range produced by these microscopic fungi includes both highly toxic ones such as zearalenone (ZEA), deoxynivalenol (DON), aflatoxins (AF B1), fumonisins (FB1 and FB2), ochratoxin A (OTA) and patulin, T-2 toxin, with their contents in food products being strictly standardized in the Customs Union countries (CU TR 021/2011) 1 and abroad [2][3][4][5][6][7][8], and emergent mycotoxins (EMT) that have not been studied enough: enniatins, bovericin, moniliformin, fuzproliferin, fusaric acid, sterigmatocystin, emodin, mycophenolic acid, alternariol and its monomethyl ether, tenuazonic acid, asperglaucid, and tentoxin, that can simultaneously occur in food products and make its toxic contribution into an end product [9][10][11][12]. Mycotoxins cause actual hazards for people as they exert carcinogenic, mutagenic, and teratogenic impacts, suppress the immune system, and can induce a number of diseases [13].…”
mentioning
confidence: 99%